Top 10 research priorities relating to aphasia following stroke. Issue 11 (2nd November 2018) - Franklin, Sue; Harhen, Dearbhla; Hayes, Michelle; Demos Mc Manus, Sasha; Pollock, Alex
ABSTRACT: Background : Pollock et al. (2014, Top 10 research priorities relating to life after stroke – Consensus from stroke survivors, caregivers, and health professionals, International Journal of Stroke, 9, 313–320) applied the James Lind Alliance methodology to derive the top 10 priorities for research relating to life after stroke. Many of the initial Treatment Uncertainties related to aphasia. Aim: The current study uses these Treatment Uncertainties to derive the shared top 10 research priorities of people with aphasia (PWA), their carers and speech and language therapists (SLTs) Methods & Procedures: Treatment Uncertainties relating to aphasia were identified from the 226 unique unanswered questions relating to life after stroke generated by Pollock et al. Using these 34 Treatment Uncertainties relating to aphasia, the last two stages of the JLA method (survey followed by consensus meeting) were carried out with PWA, their carers and SLTs. Participants ranked the top 10 priorities from the 34 given in the survey. Communication ramps were used with the PWA. The 16 highest ranked uncertainties were presented at the consensus meeting, where the final shared top 10 priorities were agreed, merging some statements and refining the wording in others. Outcomes & Results: Participants included PWA with severely affected communication. The methodology produced consensus on a range of priorities including the best treatments and most effective service delivery, management of psychosocial issues, helping volunteers and carers, and research into treating severe forms of aphasia. Conclusions: PWA are able to participate fully in research priority setting. These shared research priorities represent an excellent base for the development of clinically important research in aphasia, addressing issues which are of greatest importance to key stakeholders.